Fit to be tied - Hatcher, Robin Lee (Hatcher, Robin Lee. Sisters of Bethlehem Springs., 2009)
Cleo dresses like a cowboy, is fearless and fun-loving, and can ride, rope and wrangle as well as any man. In 1916 Idaho, those aren't talents most women aspire to. Cleo believes God's plan for her does include a husband-- but it couldn't possibly be Sherwood Stanton, could it?